Characterization of nerve and microvessel damage and recovery in type 1 diabetic mice after permanent femoral artery ligation. Issue 9 (5th May 2015) - Lozeron, Pierre; Mantsounga, Chris S.; Broqueres‐You, Dong; Dohan, Anthony; Polivka, Marc; Deroide, Nicolas; Silvestre, Jean‐Sébastien; Kubis, Nathalie; Lévy, Bernard I.
Abstract : Neuropathy is the most common complication of the peripheral nervous system during the progression of diabetes. The pathophysiology is unclear but may involve microangiopathy, reduced endoneurial blood flow, and tissue ischemia. We used a mouse model of type 1 diabetes to study parallel alterations of nerves and microvessels following tissue ischemia. We designed an easily reproducible model of ischemic neuropathy induced by irreversible ligation of the femoral artery. We studied the evolution of behavioral function, epineurial and endoneurial vessel impairment, and large nerve myelinated fiber as well as small cutaneous unmyelinated fiber impairment for 1 month following the onset of ischemia. We observed a more severe hindlimb dysfunction and delayed recovery in diabetic animals. This was associated with reduced density of large arteries in the hindlimb and reduced sciatic nerve epineurial blood flow. A reduction in sciatic nerve endoneurial capillary density was also observed, associated with a reduction in small unmyelinated epidermal fiber number and large myelinated sciatic nerve fiber dysfunction. Moreover, vascular recovery was delayed, and nerve dysfunction was still present in diabetic animals at day 28. This easily reproducible model provides clear insight into the evolution over time of the impact of ischemia on nerve and microvessel homeostasis in the setting of diabetes. © 2015 Wiley Periodicals, Inc.